Winter-Spring Development of the Zooplankton Community Below Sea Ice in the Arctic Ocean - Hop, Haakon; Wold, Anette; Meyer, Amelie; Bailey, Allison; Hatlebakk, Maja; Kwasniewski, Slawomir; Leopold, Peter; Kuklinski, Piotr; Søreide, Janne E. (Frontiers in Marine Science, 2021)
The impact of the rapidly changing Arctic on zooplankton community structure and seasonal behaviour is not yet understood. Here we examine 6 months of under-ice zooplankton observations from the N-ICE2015 expedition (January to June 2015) in the Nansen Basin and on the Yermak Plateau north of Svalbard. Stratified sampling in the water column was done with MultiNet during the entire expedition, and sampling in the upper 5 m below sea ice was performed during April-May by divers using a hand-held net. Hydrographic conditions were dominated by northward-flowing warm and saline Atlantic Water at intermediate depth, and southward-flowing cold Polar Surface Water in the upper 100 m. The mesozooplankton was dominated by copepods. Most numerous were the small ubiquitous Oithona similis in the upper 200 m, with Microcalanus spp. and Triconia borealis further down the water column. Calanus finmarchicus dominated among the Calanus species while Metridia longa was also numerous. The most abundant deep-water copepods were Paraeuchaeta spp. and Spinocalanus spp. Arrow worms (Chaetognatha) and comb jellies (Ctenophora) were the most numerous non-copepods. The mesozooplankton community was more dependent on surrounding water mass characteristics, such as salinity and depth, than geographical location. Algal food availability, which was closely linked to seasonality, explained the community changes seen in surface waters in May and June due to seasonal ascent and recruitment. Seasonal changes from winter to spring mostly involved an increase in the herbivorous C. finmarchicus and its nauplii in the upper 200 m of the water column coinciding with the peak of the phytoplankton bloom in late May. The Yermak Plateau and adjacent Nansen Basin were characterised by oceanic North Atlantic and Arctic species, many of which are deep water specialists. Despite the late onset of the spring bloom due to consolidated sea ice, both North Atlantic and Arctic species successfully reproduced in the study area. This explains the species-rich mesozooplankton community in this region as opposed to the less productive central Arctic Ocean. Future prospects of less sea ice and earlier onset of the bloom will likely be positive for the overall secondary production by both Arctic and boreal zooplankton in this region.